2016
DOI: 10.7567/apex.9.076202
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional concentration distribution of reactive oxygen species transported through a tissue phantom by atmospheric-pressure plasma-jet irradiation

Abstract: The two-dimensional concentration distribution of reactive oxygen species (ROSs) transported through an agarose-film tissue phantom by atmospheric-pressure plasma-jet irradiation is visualized using a KI-starch gel reagent. Oxygen addition to helium enhances ROS transportation through the film. A radial ROS distribution pattern at the plasma-irradiated film surface changes into a doughnut-shaped pattern after passing through the film. The ROS transportation speed is 0.14–0.2 mm/min. We suggest that there are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 32 publications
3
35
0
Order By: Relevance
“…Similarly, Toshiyuki Kawasaki et al also found a ring‐shaped distribution of ROS on a model tissue, though the model tissue was made of agarose. It was proposed that the center of the ring‐shaped pattern was the point where plasma plume contacted with the model tissue, so the short‐lived species such as O could dye the gelatin gel films by reacting with KI‐starch . This might be the reason for the generation of brown‐dyed point in the center of a ring‐shaped pattern.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Toshiyuki Kawasaki et al also found a ring‐shaped distribution of ROS on a model tissue, though the model tissue was made of agarose. It was proposed that the center of the ring‐shaped pattern was the point where plasma plume contacted with the model tissue, so the short‐lived species such as O could dye the gelatin gel films by reacting with KI‐starch . This might be the reason for the generation of brown‐dyed point in the center of a ring‐shaped pattern.…”
Section: Resultsmentioning
confidence: 99%
“…KI‐starch reagent was reported to have color‐forming reactions with ROS via the oxidation of I ‐ to I 2 , and it has been used to visualize the two‐dimensional ROS distribution after passing through a model tissue made of agarose . According to the well‐known iodine‐starch reaction, I ‐ was firstly oxidized to I 2 by ROS, and I 2 reacts with excess I ‐ to form I 3 ‐ then forms complexes with starch, which turns the color to blue.…”
Section: Experimental Setup and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the species delivered to a target, ROS are widely considered significant players in causing cellular DNA damage, even cell death, and ROS are normally cited as causing increased damage with elevated concentration . Several recent reports have shown an ability to visually determine the 2D ROS concentration on an APPJ‐treated liquid surface by using a potassium iodide (KI)‐starch reagent . Here, with a similar reagent, we quantitatively measured both the 2D distribution of ROS deposited to the liquid surface and the total amount of ROS delivered to the liquid.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of plasma intervention in biology and medicine is thought to be mainly governed by reactive oxygen species (ROS) and reactive nitrogen species (RNS), or collectively RONS [39][40][41]. Experimentally, using models of tissue fluid, tissue and cells, it has been shown that plasmagenerated RONS are not only delivered into tissue fluid but can also potentially be delivered deep within a tissue mass and across a phospholipid membrane into cells [7,[42][43][44][45][46][47][48][49][50][51][52][53]; computer simulations corroborate these experimental observations [54][55][56][57][58][59][60][61]. In the physiological environment, RONS regulate key biochemical pathways, inducing chemical and physical changes in cells [39,62].…”
Section: Introductionmentioning
confidence: 99%